POLÍTICAS PÚBLICAS DE INTEGRACIÓN, DESARROLLO Y TRATAMIENTO DE ASIMETRÍAS EN EL MERCOSUR: EL ESTUDIO DEL CASO DEL FONDO DE CONVERGENCIA ESTRUCTURAL DEL MERCOSUR - Chomont, Tamara (Revista Ética e Filosofia Política, 2018)
This is an analysis of the current Mercosur´s Structural Convergence Fund (FOCEM) through the implementation of asymmetry treatment public policy, which aim is to counter effect the structural imbalance within the block´s various country members. It is all conceived in the context of the Fund´s origin, its composition, its programs, and its implications within Mercosur´s regional development new public policy phase. The purpose of this document is to draw some notions from FOCEM´s asymmetry treatment work along with the various states´active role towards Mercosur deeper integration.